THE EVOLUTIONARY DYNAMICS OF SEXUALLY ANTAGONISTIC MUTATIONS IN PSEUDOAUTOSOMAL REGIONS OF SEX CHROMOSOMES - Brian Charlesworth; Crispin Y. Jordan; Deborah Charlesworth (2014)
Sex chromosomes can evolve gene contents that differ from the rest of the genome, as well as larger sex differences in gene expression compared with autosomes. This probably occurs because fully sex-linked beneficial mutations substitute at different rates from autosomal ones, especially when fitness effects are sexually antagonistic (SA). The evolutionary properties of genes located in the recombining pseudoautosomal region (PAR) of a sex chromosome have not previously been modeled in detail. Such PAR genes differ from classical sex-linked genes by having two alleles at a locus in both sexes; in contrast to autosomal genes, however, variants can become associated with gender. The evolutionary fates of PAR genes may therefore differ from those of either autosomal or fully sex-linked genes. Here, we model their evolutionary dynamics by deriving expressions for the selective advantages of PAR gene mutations under different conditions. We show that, unless selection is very strong, the probability of invasion of a population by an SA mutation is usually similar to that of an autosomal mutation, unless there is close linkage to the sex-determining region. Most PAR genes should thus evolve similarly to autosomal rather than sex-linked genes, unless recombination is very rare in the PAR.